HUBUNGAN KARAKTERISTIK IBU DENGAN STATUS GIZI BALITA DI WILAYAH KERJA PUSKESMAS WALANTAKA KOTA SERANG TAHUN 2019 - Qonita; Umalihayati (Poltekkes 'Aisyiyah Banten, 2020)
Weighing under five is very important for early detection of cases of malnutrition and malnutrition. By diligently weighing a toddler, the growth of a toddler can be monitored intensively so that if a child's weight does not rise or if a disease is found, recovery and prevention efforts can be made immediately so that it does not become malnourished or malnourished. The sooner it is found, the handling of cases of malnutrition or poor nutrition will be better. Quick and appropriate handling according to the case management of malnourished children will reduce the risk of death so that mortality due to malnutrition can be suppressed. Based on data obtained from the Serang City Health Office, the average BGM for underfive cities in 2016 was 1.06%. Walantaka Puskesmas is one of the Puskesmas that has a Lower Red Line (BGM) rate above the city average of 1.3% and 4 of its people were found to be malnourished. This study aims to determine the relationship of maternal characteristics with the nutritional status of children under five in the Walantaka Community Health Center in Serang in 2019. The research design used was analytical research with cross sectional approach where the dependent variable was the nutritional status of children under five and the independent variables were education, knowledge and behavior of mothers regarding nutritional status. The population in this study amounted to 4,880 people and the sample used was 98 respondents with a sampling technique in this study using accidental sampling technique. The results obtained, the characteristics of mothers associated with the nutritional status of toddlers are education (p-value = 0.002), knowledge (p-value = 0,000) and behavior (p-value = 0,000). Coordination needs to be cross-program and cross-sectoral, one of which is trying to improve health services by continuing counseling aimed at mothers who have children aged 1-5 years about the importance of nutrition which will have an impact on the nutritional status of children aged 1- 5 years in its golden age, and provide health education guidance for cadres to work together in promoting malnutrition eradication programs, this aims to motivate mothers to want to provide nutritious food to children aged 1-5 years. Also carried out coaching that continues for areas that are vulnerable to nutrition